“A Study to Assess the Effectiveness” of Planned Teaching Programme on Knowledge and Practice Regarding Buerger Allen Exercise Among Traffic Police with Diabetes Mellitus of Selected Urban Areas” - Rawat, Neelam; Gholap, Gayatri (International Journal of Nursing Research, 2023)
Background: Occupational health workers spending most of the day on their feet, every working day are at greater risk of health problems including varicose vein, poor circulation and swelling in the feet’s and legs, foot problems, and joint damage. Early detection of the condition could lead to treatment that offers the potential to reduce the incidence of fatal as well as to also improve the quality of life. Aim: The aim of the study was to assess knowledge and practice regarding Buerger Allen exercise on the lower extremity perfusion among traffic police before and after planned teaching. Methodology: Quantitative (descriptive evaluatory) research approach and one group pre-test- post-test research design (pre-experimental) is used. The study was conducted in selected urban areas of Mumbai with sample consisted of 60 traffic police personnel. Structured questionnaire was prepared to assess knowledge and self-reported questionnaire was used to assess practice. Planned teaching program with demonstration on Buerger Allen exercise was the intervention of the study provided to the samples. Results: The overall pre-test mean knowledge score and the overall pre-test mean practice score was found to be 8.42. The overall post-test mean knowledge score and practice score was found 15.05 and 6.48, respectively. The “t” value (P = 0.05) for knowledge score was 18.21 and for practice score 24.87 which indicates the effectiveness of planned teaching program regarding Buerger Allen exercise.